Chinese translation of Nadja M. Alexander (ed.), Global trends in mediation (2nd Edition) (全球调解趋势（第二版）[澳] 娜嘉.亚历山大 主编 王福华 魏庆玉 译) - ALEXANDER, Nadja (Institutional Knowledge at Singapore Management University, 2006)
In its first edition, Global Trends in Mediation was the first book to concentrate on mediation from a comparative perspective - reaching beyond the all-too-familiar Anglo-American view - and as such has enjoyed wide practical use among alternative dispute resolution (ADR) practitioners worldwide. This new edition has not only been updated throughout; it has also added two new jurisdictions (France and Quebec) and a very useful comparative table summarising the salient points from each of the fourteen jurisdictional chapters.